Development of Digital Flashcards Assisted by Augmented Reality on Doppler Effect and Polarization Material - Siahaan, Sardianto Markos; Nugraha, Agung Malsen (Universitas Dharma Wacana, 2024)
Augmented reality-assisted digital flashcards on doppler effect and polarisation materials that are valid and practical have been successfully developed. This research uses Rowntree's development procedure which consists of three stages: planning stage, development stage and evaluation stage. The evaluation stage in this study uses Tessmer's formative evaluation stage which consists of stages: self evaluation, expert review, one to one evaluation, and small group evaluation. Data collection techniques used walkthroughs and questionnaires. The validity level of this digital flashcard was assessed by three experts, namely material aspect experts, digital flashcard design aspect experts, and augmented reality design aspect experts. The results of the digital flashcard expert validation test at the expert review stage obtained data on the material aspect of 97.75% with a very valid category, the digital flashcard design aspect of 95.75% with a very valid category, and the augmented reality design aspect of 81.5% with a valid category. While the teacher's response was 94.67%, at the one to one evaluation stage an average rating of 86% was obtained in the practical category. At the small group evaluation trial stage, the average assessment result was 87% with a very practical category. Thus, digital flashcards assisted by augmented reality on Doppler effect and polarisation material are declared valid and practical.